Virtual Screening and Synthesis of New Chemical Scaffolds as VEGFR-2 Kinase Inhibitors - Elsayed, M. S.; El-Araby, M. E.; Serya, R. T.; Abouzid, K.A. M. (Arzneimittelforschung, 2012)
VEGFR-2 tyrosine kinase inhibitors are currently receiving high interest in drug discovery process as anticancer agents. We have used virtual screening techniques in order to discover new scaffolds that can be used for developing new VEGFR-2 kinase inhibitors.Similarity ensemble approach was used to reduce the chemical space of ZINC database to select a subset of compounds. A validated structure-based pharmacophore was developed and adopted to screen the selected subset. Initial hits mapped to the pharmacophore were filtered using docking and scoring. Selected compounds were synthesized and biologically tested. Compound 9 showed very good cytotoxicity profile against the NCI 60 cancer cell lines, while compound 8 showed reasonable inhibition of VEGFR-2 tyrosine kinase.Stepwise virtual screening of databases such as ZINC may result in new scaffolds for developing VEGFR-2 kinase inhibitors.
Keywords: SEA prediction; pharmacophore; docking; VEGFR-2